Stalking behavior: an overview of the problem and a case report of male-to-male stalking during delusional disorder - Dreßing, Harald; Henn, Fritz A.; Gass, Peter (Psychopathology, 2002)
Stalking is a widespread phenomenon describing a pattern of intrusive and threatening behavior leading to the victim’s perception of being harassed and rendered fearful. This paper outlines relevant aspects of the stalking concept and reviews the historical development of this categorization, different typologies of stalking behavior, associated psychiatric diagnoses, frequency and demographic data, psychomedical impact on the victims and therapeutic approaches. Special gender aspects are discussed by presenting a case history of male-to-male stalking.